Improving Fantasy Story Reading Skills Through the Application of the Picture and Picture Method in Class VII Students of SMP Negeri 3 Dusun Utara - Hespiyani Hespiyani (Journal of Educational Sciences, 2026)
The background of the research is that the Indonesian language learning process at SMPN 3 Dusun Utara class VII uses the lecture method and learning outcomes are relatively low. The study aims to improve the fantasy story reading skills of class VII students of SMPN 3 Dusun Utara through the application of the picture and picture method. The type of research is Classroom Action Research (CAR) with two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 30 students of class VII in the odd semester of the 2025/2026 academic year. The research was conducted at SMPN 3 Dusun Utara. Data collection techniques were observation, reading tests, and documentation. The results of the study are the results of the pre-action test, namely the average value of 64.97. The results of the cycle I test, the average value of 70.80. The results of the cycle II test, the average value of 80.37. Learning completeness in the pre-action (46.67%), cycle I (73.33%), and cycle II (100%). The conclusion of the study is that the picture and picture method is effective in increasing students' activeness, interest, and learning outcomes in reading fantasy stories.